(3ebGJd GdWGdHjfs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj,J (B356 (3g` s ((3eMeO cGXe Hf TQja HgGA GdOjf s)
(3ChdgG (B:s
(3bGd Ydi Hf GdMSjf GdCUagGfi GdeDda dgPG GdcJGH HYO MeO Gddg hGdKfGA Ydjg jaJJM cd cdGe hjHJOC cd ebGd GQTGO LedkG ef CNHGQ ef bJd ef hdO CHj WGdH s
(3BNQgG (B:s
(3hcGf cd ef NGda gPg GdSHjd hbJd Ydi VOgG efge jSJJQ NHQg hjNai CeQg hfSCd Gddg GdYUeI hgh MSHfG hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3Ydjg cKjQ ef GdJedcGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B78s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eMeO Hf YHO GdQMef GdYHjcGf GdNGUI HGdQjGV(B(920 (3C (B/ 211) s
Keywords: (3GdJGQjNs